Engaging adolescents and young adults in decisions about return of genomic research results: study protocol for a mixed-methods longitudinal clinical trial protocol - Amy A. Blumling; Michelle L. McGowan; Cynthia A. Prows; Kristin Childers-Buschle; Lisa J. Martin; John A. Lynch; Kevin R. Dufendach; Ellen A. Lipstein; Melinda Butsch Kovacic; William B. Brinkman; Melanie F. Myers (BMC Medical Informatics and Decision Making)
Abstract Background To protect minors’ future autonomy, professional organizations have historically discouraged returning predictive adult-onset genetic test results and carrier status to children. Recent clinical guidance diverges from this norm, suggesting that when minors have genomic sequencing performed for clinical purposes, parents and children should have the opportunity to learn secondary findings, including for some adult-onset conditions. While parents can currently opt in or out of receiving their child’s secondary findings, the American Society of Human Genetics Workgroup on Pediatric Genetic and Genomic Testing suggests including adolescents in the decision-making process. However, it is not clear what factors young people consider when given the opportunity to learn genetic findings for themselves. In this manuscript, we report on the methods for a clinical trial that examines adolescents’, young adults’, and their parents’ decisions about learning genomic information for the adolescent or young adult. Methods We are enrolling assenting (ages 13–17) adolescents and consenting (ages 18–21) young adults in a prospective genomic screening study to assess the choices they make about receiving individual genomic results. Participants use an online tool to indicate whether they want to learn their personal genetic risk for specific preventable, treatable, and adult-onset conditions, as well as carrier status for autosomal recessive conditions. We are examining (1) how choices differ between adolescent and young adult cohorts (as well as between adolescents/young adults and parents) and (2) decisional conflict and stability across study timepoints. Results are returned based on participants’ choices. Qualitative interviews with a subset of participants explore decisional stability, adolescent/young adult engagement with parents in decision-making, and the impact of learning pathogenic/likely pathogenic and autosomal recessive carrier results. Discussion This study explores decision making and decision stability between adolescents and parents (where applicable), as well as the ethical implications and impact of return of clinical-grade genetic research results to adolescents and young adults. The results of this study will contribute empirical evidence to support best practices and guidance on engaging young people in genomic research studies and clinical care that offer return of results. Trial registration ClinicalTrials.gov Identifier: NCT04481061. Registered 22 July 2020.